Locality Improvement Scheme Based on QR Code Technique within Inverted Index - Alyousif, Aya Abdulhussein; Yassin, Ali Adil (Informatica, 2023)
Searchable symmetric encryption is one of the most important modern technologies that allow the owner to store private data on an unreliable server and search for the data securely while preserving the data’s confidentiality and privacy. This field has several schemes, but these schemes suffered from slower data retrieval in the case of large database sizes owing to the poor locality. Hence, the server visits several memory locations for a single query. Other studies focused on improving the locality, but the result is either increased storage capacity or decreased efficiency of data reading. In the present study, we present a secure, searchable scheme that overcomes the abovementioned issues and works to improve the locality by exploiting the QR code technique and the Advanced Encryption Standard algorithm. Furthermore, our work maintains read efficiency, helps reduce the risk of data breaches, and protects sensitive information from being accessed by unauthorized individuals. Moreover, the proposed scheme can resist cyber security attacks, such as frequency analysis attacks and keyword guessing attacks. Additionally, we used real-world data in our experiments and demonstrated that our proposed scheme is secure and practically efficient and holds high accuracy.